INDEPENDENT FAMILY PLANNING IN RURAL AND URBAN AREAS GRESIK DISTRICT - Yuly Sulistyorini; Nunik Puspitasari; Diah Indriani; Rachmah Indawati (UNEJ e-Proceeding)
Based on the results of IDHS 2012 showed for thefirst time for 7 times IDHS since 1987, Indonesia TFR(Total Fertility Rate) figures currently show adownward trend, but settled (stagnant) in the figureof 2.6 per woman until 2012. [1] The IDHS resultscan be seen in Figure 1.Figure 1. Tren TFR Indonesia, 1991 – 2012 (IDHS 2012)Figure 1. shows that the TFR of 2.6, which meansthat every woman until the end of her reproductivelife on average have 2.6 children. It has the potentialoccurrence of higher birth rates in the comingdecades. Results Demographic and Health Survey2012 showed that the TFR in East Java today hasincreased rather than IDHS 2007 of from 2.1 to2.3.[2] Considering this, the family planning programneeds serious attention, given the increase ofpopulation in Indonesia requires the setting andsubsistence good and decent. The success in theimplementation of family planning programs isinfluenced by several factors. Presence Extension FPand the support of government / local governmentsis crucial. Besides the role of the public to participatedirectly in the program is also a key to the success ofthe program. Participation of the community asparticipants in the program experienced afluctuating conditions, when at this time arerequired to be more independent in getting familyplanning services. Funding for family planningservices should be paid by the communitiesthemselves. On the other hand, after the economiccrisis hit the country, resulting in the price of goodshas increased and lower purchasing power. Thisgives a huge impact on society, especially inspending money and setting priorities in thehousehold. This will lead to two possibilities weredone by the people, namely, the first is a higherincidence of drop-out users of contraceptives andthe second is a change in use of contraceptives fromeffective to ineffective. Moreover, the existence ofsubsidies for contraceptives at this time is verylimited. FP independently be one option for peoplewho want use FP including for people in rural andurban areas. Conditions rural and urban havedifferent characteristics. The rural tends to beholding culture / customs, do not easily accept newthings, facilities and infrastructure is not as completeas in urban area, education is still relatively low. [3]Gresik district is one of district in East Java with theachievements of TFR were categorized high at 2.20in 2012. Even in 2013 based on data reportsacceptors in East Java Legislative BKKBN (2013) theaddition of new family planning acceptors is quitelow at 15 % compared to other districts.Therefore, it is necessary to study the conditions ofrural and urban communities in Gresik inIndependent Family Planning (FP).